2018
DOI: 10.3390/su10051429
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in the Minerals Industry: Seeking a Consensus on Its Meaning

Abstract: Sustainability science has received progressively greater attention worldwide, given the growing environmental concerns and socioeconomic inequity, both largely resulting from a prevailing global economic model that has prioritized profits. It is now widely recognized that mankind needs to adopt measures to change the currently unsustainable production and consumption patterns. The minerals industry plays a fundamental role in this context, having received attention through various initiatives over the last de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 124 publications
(438 reference statements)
0
19
0
1
Order By: Relevance
“…From a normative perspective, better climate change responses in mining regions offer some hope of more sustainable development in a climate-resilient future (Addison, 2018; Ali et al , 2017; Giurco & Cooper, 2012; Hodgkinson & Smith, 2018; Segura-Salazar & Tavares, 2018). Viewed more critically, mining regions face the twin challenges of sustainability and justice.…”
Section: Introductionmentioning
confidence: 99%
“…From a normative perspective, better climate change responses in mining regions offer some hope of more sustainable development in a climate-resilient future (Addison, 2018; Ali et al , 2017; Giurco & Cooper, 2012; Hodgkinson & Smith, 2018; Segura-Salazar & Tavares, 2018). Viewed more critically, mining regions face the twin challenges of sustainability and justice.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, mining is the human activity that has been more disturbing to environment and is linked to large social impacts and inequalities." More tellingly, Segura-Salazar and Tavares (2018) suggested that "when compared to other resource industries such as forestry, aquaculture and agriculture, the mining industry is perceived as one of the least committed to sustainable development." On the other hand, sustainable development is typically defined as development "that meets the needs of the present without compromising the ability of future generations to meet their own needs" (World Commission on Environment and Development, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Here, "prioritizing the preservation of nature is pre-eminent" (Hudson, 2005). However, there is growing interest in the relationship between minerals and mining and sustainability and in seeking "a consensus on the implications of sustainability in the minerals industry" (Segura-Salazar & Tavares, 2018). In a recent study of Corporate Social Responsibility (CSR) practices in the Portuguese mining industry, Gaspar Alves and Mendes Rodrigues (2017), for example, noted "results suggest that CSR practices are not integrated in the management control system, are not part of a long-term environment strategy, and only reflect compliance with Portuguese legislation."…”
Section: Introductionmentioning
confidence: 99%
“…In the minerals industry, sustainability can be approached from two perspectives, with the second building upon the first. One is focused on sustainable resource use and management during operations (i.e., sustainable functioning as described by [22]), and the other is focused on minimizing the social and environmental impacts of the mining project during and after operations (i.e., sustainable development as described by [22,23]). These concepts have been more broadly developed in industries that use renewable resources (e.g., the fashion industry [24]).…”
Section: Introductionmentioning
confidence: 99%